Narrowing the Farm-to-Plate Knowledge Gap through Semiotics and the Study of Consumer Responses Regarding Livestock Images - Joy N. Rumble; Emily B. Buck (Journal of Applied Communications, 2013)
It has been suggested that a farm-to-plate knowledge gap exists between farmers and consumers. In addition, previous studies have concluded that U.S. citizens do not have accurate knowledge or perceptions about agriculture. It is thought that this absence of knowledge and existing misconceptions may be due to the images consumers see regularly through the media. In this research study, researchers used a directly administered questionnaire to evaluate consumers’ responses regarding the comparison of two livestock images. The study was conducted at the 2009 Ohio State Fair. Through voluntary participation, research participants answered questions regarding their perceptions of traditional and conventional livestock housing methods by viewing two images. In addition, participants were asked to justify each of their responses through oral reasoning. Questionnaires were completed by 508 participants, of which 502 were deemed usable. Results indicate participants are somewhat knowledgeable about livestock housing methods, but the perceptions and justifications of the respondents are not always accurate. The results also indicate agricultural images, as well as images regularly seen in the media, may influence such perceptions. In order to narrow the farm-to-plate knowledge gap, it is important for the agriculture industry to effectively improve the knowledge and perceptions of agriculture amongst consumers.
Keywords: semiotics; directly administered questionnaire; agricultural knowledge; agricultural perceptions; images; knowledge gap theory